Gregory's forgotten rebel: the portrayal of Basina by Gregory of Tours and its implications. Issue 2 (14th March 2022) - Singer, Rachel
Abstract : Scholars of Gregory of Tours have paid little regard to the specific role of Basina in the nuns' rebellion at Sainte‐Croix abbey in Poitiers. Their inattention mirrors Gregory's narrative of the 'scandal', which presents Basina as Clotild's more passive and reluctant sidekick, whereas the judgement of the bishops' tribunal that tried the rebellion's leaders characterizes them as equally blameworthy. This article examines Basina's role in the 'scandal' in detail and argues that she was a more active participant than Gregory chose to suggest. It then seeks to explain why Gregory minimized Basina's involvement and examines what his portrayal of her contributes to our understanding of his manipulation of historical events.